THE MODEL OF ENTREPRENEURIAL MARKETING (EM) AMONG AGROPRENEURS IN THE EMERGING MARKETS: A CONCEPTUAL FRAMEWORK (Revista Galega de Economía)
Purpose â€“ This research aims to give an opportunity, value creation and innovation to the agropreneurâ€™s model farm in the emerging markets in implementing the new cost reduction practices in their farms using organic fertilizer.